2006
DOI: 10.1002/lt.20809
|View full text |Cite
|
Sign up to set email alerts
|

Surgical injuries of postmortem donor livers: Incidence and impact on outcome after adult liver transplantation

Abstract: The exact frequency and clinical consequences of surgical hepatic injuries during organ procurement are unknown. We analyzed the incidence, risk factors, and clinical outcome of surgical injuries in 241 adult liver grafts. Hepatic injuries were categorized as parenchymal, vascular, or biliary. Outcome variables were bleeding complications, hepatic artery thrombosis (HAT), and graft survival. In 82 livers (34%), 96 injuries were detected. Most injuries were minor, but clinically relevant injuries were detected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
60
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(68 citation statements)
references
References 8 publications
7
60
1
Order By: Relevance
“…The incidence of hepatic artery injury in procurement was significantly higher in grafts with aberrant arterial anomaly and arterial injury was associated with an increased risk of arterial thrombosis [36]. One of our cases had an aberrant RLA arising from the middle hepatic artery.…”
Section: Discussionmentioning
confidence: 55%
“…The incidence of hepatic artery injury in procurement was significantly higher in grafts with aberrant arterial anomaly and arterial injury was associated with an increased risk of arterial thrombosis [36]. One of our cases had an aberrant RLA arising from the middle hepatic artery.…”
Section: Discussionmentioning
confidence: 55%
“…6 Arterial injuries may be more frequent (12%) in grafts that have aberrant anatomy and may cause HAT after transplant. 1 The present cases suggest a possible strategy to address graft damage, especially presence of dHAT. If thrombosis is present in 1 aberrant vessel, the graft may be used after resection of the affected segments (cut-down liver graft).…”
Section: Discussionmentioning
confidence: 74%
“…Arterial injuries sustained during organ procurement occur in 1% to 12% transplants and contribute to the discarding of the graft. 1 These injuries are more common in the presence of abnormal anatomy and grafts from donation after circulatory death (DCD).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study has shown that injury to the hepatic veins occurs in up to 3% of deceased donor liver recoveries. 9 When we are considering the anatomy of the suprahepatic vena cava, it is important to remember that the origin of the right hepatic vein is only 0.86 cm on average from the overlying diaphragm. 5 Just distal to the ostium of the right hepatic vein lies the confluence of the middle and left hepatic veins, which lie on the left anterolateral surface of the IVC.…”
Section: To the Editorsmentioning
confidence: 99%